CRIMINAL ACCOUNTABILITY FOR BENEFICIAL OWNERSHIP OF CORPORATIONS IN THE CRIME OF MONEY LAUNDERING IN INDONESIA - Baharudin, Achmad Khozin; Kartika, Adhitya Widya (Institut Agama Islam Negeri Bone, 2023)
The development of economic globalization in a country requires a role and strengthening in order to synergize commitments through predetermined steps to harmonize economic stability and is expected to be able to face the country's economic crisis. Beneficial Ownership (BO) has the opportunity to commit a criminal act of money laundering through nominee mode so that the original identity is not known by placing dirty assets in the form of shares in the corporation so that the corporation acts as a vehicle for the crime. This research is conducted through the normative juridical method. Research using library materials by examining a legal regulation, doctrine from experts, or theories that intersect with the subject matter of discussion. The results showed that the form of responsibility looks at who is related to money laundering. The theory of corporate liability is included in limited liability. In principle, limited liability is intended for legal subjects in corporations that commit criminal acts regardless of the mistakes made but meet the elements of the Article in criminal law. Because the position of beneficial ownership is not yet effective and is still gray in the corporation, in beneficial ownership criminal liability uses strict liability, which is the punishment of criminals on the condition of considering the criminal acts committed with the rules of criminal imposition (legality) without seeing the inner attitude of the perpetrator.